If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -1 = -131 + 7x Reorder the terms: -1 + -6x = -131 + 7x Solving -1 + -6x = -131 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1 + -6x + -7x = -131 + 7x + -7x Combine like terms: -6x + -7x = -13x -1 + -13x = -131 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 + -13x = -131 + 0 -1 + -13x = -131 Add '1' to each side of the equation. -1 + 1 + -13x = -131 + 1 Combine like terms: -1 + 1 = 0 0 + -13x = -131 + 1 -13x = -131 + 1 Combine like terms: -131 + 1 = -130 -13x = -130 Divide each side by '-13'. x = 10 Simplifying x = 10
| x/6+3/x=2x/3+25/2 | | 183.75/15 | | 15y-8-3y=16 | | y=1/2x^2-4 | | 15/183.75 | | -8x-14= | | 2.4/s=0.3 | | 16x^5-x^3=0 | | 5x^2+17x+12=0 | | 1/5(-10x) | | 2x^2/3=6 | | 4+2n-2=9n+10-5n | | 9x+1x=7x+5 | | 5m+4m= | | 8/9x=8 | | 4a+5=2a+3 | | 5/3x^2+9/3x | | 2x^3-3x^2-54x=0 | | 4x-3(2x-4)=2x+4 | | -x+6=2x-30 | | 2x+2=10+x | | -72+2x^2=0 | | 6/10=9/x | | 8+m/2=-1 | | 45=5/6d | | logx-log(x+7)=1 | | 17=2e^4x | | 34=t+-55 | | 7+y=47 | | 8t+11t=133 | | 4x-13=2x+49 | | 2.4(m-3)3.8=-8.2 |